Enteric Viruses in Surface Waters from Argentina: Molecular and Viable-Virus Detection - Masachessi, Gisela (2018)
Water resources contaminated with wastewater are an important source for the dissemination of enteric viruses with an impact on the health of the population. The aim of the study was to assess the viral contamination of freshwater from a dam in Argentina by using infectious enterovirus detection, viral RNA amplification, and a genetic characterization of five enteric viruses associated with diarrhea and hepatitis. Enterovirus infectivity (iEV) was evaluated by cell culture and direct immunofluorescence. The detection of the viral genome of rotavirus (RV), human astrovirus (HAstV), norovirus (NoV), hepatitis A virus (HAV), and hepatitis E virus (HEV) was performed by reverse transcriptase PCR (RT-PCR). A total of 48 water samples from 4 monitoring points on the body of the dam from January to December 2012 and 66 water samples from 3 tourist beaches on the edge of the dam from October 2013 to October 2015 were collected monthly. During the first period, the overall viral frequency detection was 52.1% for group A RV, 50% for HAstV, 60.4% for NoV, 22.9% for HAV, 2.1% for HEV, and 64.6% for iEV. The overall frequency detection for the second sampling was 18.2% for RV and HAstV, 31.8% for NoV, 7.57% for HEV, and 66.7% for iEV. There was no detection of HAV during this period. The genotypes and genogroups detected through the study correlated with the most common genomic variants associated with human gastrointestinal and hepatitis illnesses. The results obtained could alert the health systems and environmental sanitation to make decisions for viral control and prevention in our environment.